Can Personal Values Help to Manage Workers' Occupational Safety and Health Behaviour?. (2017) - Manu, Patrick; Mahamadu, Abdul-Majeed; Hadikusumo, Bonaventura; Leungbootnak, Narong; Gibb, Alistair; Bell, Nick
Abstract: Finding innovative and effective ways of improving construction workers' occupational safety and health behaviour is a challenge for implementers of behavioural-based safety (BBS) programmes. Whilst innate antecedents of behaviour could hold the key, limited research has explored the potential effect of innate triggers of behaviour such as personal values. In order to address this gap, this study presents findings from two exploratory inquiries (in UK & Thailand) into the influence of workers personal values on occupational safety and health motivation (OSHM). Both inquiries employed surveys of construction workers on project sites. The UK and Thailand surveys yielded 55 and 83 responses respectively. Through the use of factor analysis and multiple regression modelling, it was found from both surveys that various dimensions of higher-order personal values have statistically significant relationships with different dimensions of OSHM. For instance, in the Thai study self-transcendence and conservation values were positively related to identified OSHM and intrinsic OSHM respectively, while self-enhancement value was positively related to introjected OSHM. In the UK survey, intrinsic and identified motivation scales loaded as one dimension (autonomous motivation) which was positively related to self-transcendence. Overall, the findings from the different national contexts provide some evidence of the predictive effect of personal values on OSHM. The findings thus begin to emphasise the need for the consideration of workers personal values in the design/development and implementation of BBS interventions.